SAUDI ARABIA AND TÜRKIYE ‘S POLICY TOWARDS HAMAS: BETWEEN PRAGMATISM AND REGIONAL GEO-POLITICAL BALANCE - Hannase, Mulawarman; Rohman, Syaiful (Universitas Padjadjaran, 2026)
This article analyzes the foreign policies of Saudi Arabia and Türkiye toward Hamas during the 2020–2025 period, marked by regional realignments, the Abraham Accords, and renewed escalation in Gaza. As a central non-state actor in the Palestinian–Israeli conflict, Hamas has generated divergent responses among key Muslim-majority states. This study examines how ideological orientation, regime security concerns, and regional geopolitical calculations shape Saudi and Turkish policy choices. Employing a qualitative descriptive analytical approach and a desk study method, the research draws on official government statements, diplomatic documents, reports from international policy institutions, and peer-reviewed academic literature. The findings show that Saudi Arabia maintains political distance from Hamas due to its association with the Muslim Brotherhood, concerns over domestic and regional stability, and a preference for state-centric diplomacy through the Palestinian Authority as the sole legitimate representative of the Palestinian people. In contrast, Türkiye sustains political engagement with Hamas, reflecting ideological affinity with political Islam and an activist foreign policy aimed at advancing regional influence. Comparatively, this study argues that Saudi Arabia’s Hamas policy is primarily driven by regime-security pragmatism, whereas Türkiye’s approach reflects the ideological instrumentalization of the Palestinian issue, producing distinct foreign policy trajectories despite shared rhetorical support for Palestine. These findings highlight fragmentation among Muslim-majority states and demonstrate how the Palestinian issue has become an arena of regional ideological competition rather than policy convergence.